Molecular phylogeny of endophytic Dendryphiella: In quest of finding out ancestor of important rice seed micro-flora - Sethi, Arundhati B; Dhua, Urmila; Mukherjee, Arup Kumar; Jena, Mayabini; Dhua, Sudhiranjan; Samanta, Soma (ORYZA-An International Journal of Rice, 2018)
Thirteen endophytic non sporulating fungi present in healthy seeds of rice cultivars, popular in coastal India, were isolated by 'host tissue transplant' method. Those were identified by the molecular technique and phylogenetic analysis by Phylogeny fr software was done. The phylogeny tree of 32 taxa including 27 Dendryphiella species and five Cochliobolus miyabeanus spp. was rendered. There were two major groups. Five Cochliobolus miyabeanus spp. (out group ) were together the smaller cluster whereas all the Dendryphiella species with same internal node. The Dendryphiella group was further subdivided in two sub groups where 10 marine Dendryphiella and 17 terrestrial endophytic Dendryphiella grouped in two different sister groups. The high bootstrap values for each subcluster justified their grouping in the proper bunch. This analysis indicated that marine and 'terrestrial endophytic Dendryphiella' had common ancestors.